Phylogenetic and morphological infrageneric classification of the genus Dendroceros (Dendrocerotaceae; Anthocerotophyta), with the addition of two new subgenera. Issue 7 (3rd October 2019) - Peñaloza-Bojacá, Gabriel Felipe; Villarreal-Aguilar, Juan Carlos; Maciel-Silva, Adaíses Simone
Abstract : Dendroceros is one of the most diverse genera of hornworts, with 41 species and a widespread distribution. The genus is highly distinctive by its epiphytic habitat, gametophytes with perforated wings, multicellular spores due to endosporic germination, highly modified pyrenoid, and desiccation tolerance. The genus is monophyletic and, until now, was divided into two subgenera (subg. Apoceros and subg. Dendroceros ). This classification has not been tested within a phylogenetic framework. Using published phylogenetic data from four molecular markers ( rbcL, trnK including matK, rps4, and nad5 ) as well as morphological observations of over 80 specimens, we chose 38 morphological characters, which were mapped in the best maximum likelihood tree and optimized for reconstruction of ancestral character. We circumscribe the genus Dendroceros and propose 4 subgenera: subg. Apoceros (eight species), characterized for having schizogenous cavities in the midrib; subg. Dendroceros (14 species) with undulate-crispate gametophyte wings, and spore distal surface covered by aculeate papilla; subg. Nodulosus (five species) with rectangular cells in the capsule with nodular wall thickenings; and the monotypic subg. Cichoraceus with a single species that has granular spore micro-ornamentations, and a macro-ornamentation formed by pustulate papilla.